2020
DOI: 10.1109/taslp.2020.2969779
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-Driven Binaural Beamforming Using EEG-Based Auditory Attention Decoding

Abstract: The performance of speech enhancement algorithms in a multi-speaker scenario depends on correctly identifying the target speaker to be enhanced. Auditory attention decoding (AAD) methods allow to identify the target speaker which the listener is attending to from single-trial EEG recordings. Aiming at enhancing the target speaker and suppressing interfering speakers, reverberation and ambient noise, in this paper we propose a cognitive-driven multi-microphone speech enhancement system, which combines a neural-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 53 publications
(50 reference statements)
0
26
0
Order By: Relevance
“…Different speech streams are represented as separate auditory objects in the brain [Shinn-Cunningham, 2008] and the representation of the attended speaker is stronger [O'Sullivan et al, 2015]. Machine learning techniques have been successfully applied to EEG recordings to determine to which of multiple speakers the listener is attending, which can be used to steer the directional gain and noise suppression in so-called neuro-steered hearing devices [Van Eyndhoven et al, 2016;Das et al, 2018;Geirnaert et al, 2019;Aroudi and Doclo, 2020]. While most of the published research so far has focused on neuro-steered hearing aids, it has been shown that AAD in CI users is feasible [Nogueira et al, 2019;Paul et al, 2020].…”
Section: Adapt Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different speech streams are represented as separate auditory objects in the brain [Shinn-Cunningham, 2008] and the representation of the attended speaker is stronger [O'Sullivan et al, 2015]. Machine learning techniques have been successfully applied to EEG recordings to determine to which of multiple speakers the listener is attending, which can be used to steer the directional gain and noise suppression in so-called neuro-steered hearing devices [Van Eyndhoven et al, 2016;Das et al, 2018;Geirnaert et al, 2019;Aroudi and Doclo, 2020]. While most of the published research so far has focused on neuro-steered hearing aids, it has been shown that AAD in CI users is feasible [Nogueira et al, 2019;Paul et al, 2020].…”
Section: Adapt Settingsmentioning
confidence: 99%
“…These are important characteristics to consider for the future integration of EEG systems into cochlear implants, and may guide design decisions for optimal measurement of objective measures using CIs. Potential applications of EEG-CI systems are chronic neuro-monitoring of CI users, remote fitting and diagnostics, and so-called neuro-steered hearing devices [Van Eyndhoven et al, 2016;Geirnaert et al, 2019;Aroudi and Doclo, 2020], which autonomously adapt their fitting based on responses from the user's brain.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there was a mismatch between acoustic conditions in the AAD experiments and the audio processing modules. In [23], speech enhancement was achieved using binaural direction-of-arrival (DOA) estimators with linearly constrained minimum variance (LCMV) beamformers. The AAD module used EEG signals recorded in two relatively high signal-to-noise ratio (SNR) conditions and two reverberation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The audio processing in [20,22,23] is based on linear beamforming and linear source separation techniques, which do not require any training data and have the advantage of being computationally cheap. In recent years, DNN-based approaches have become a popular alternative to solve the speaker separation problem, particularly for the challenging single-microphone scenario [24][25][26] and the even more challenging scenario with additional background noise [27,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation